Capsule carbohydrate structure determines virulence in Acinetobacter baumannii - Talyansky, Yuli (PLoS Pathog, 2021)
Acinetobacter baumannii is a highly antibiotic-resistant bacterial pathogen for which novel therapeutic approaches are needed. Unfortunately, the drivers of virulence in A. baumannii remain uncertain. By comparing genomes among a panel of A. baumannii strains we identified a specific gene variation in the capsule locus that correlated with altered virulence. While less virulent strains possessed the intact gene gtr6, a hypervirulent clinical isolate contained a spontaneous transposon insertion in the same gene, resulting in the loss of a branchpoint in capsular carbohydrate structure. By constructing isogenic gtr6 mutants, we confirmed that gtr6-disrupted strains were protected from phagocytosis in vitro and displayed higher bacterial burden and lethality in vivo. Gtr6+ strains were phagocytized more readily and caused lower bacterial burden and no clinical illness in vivo. We found that the CR3 receptor mediated phagocytosis of gtr6+, but not gtr6-, strains in a complement-dependent manner. Furthermore, hypovirulent gtr6+ strains demonstrated increased virulence in vivo when CR3 function was abrogated. In summary, loss-of-function in a single capsule assembly gene dramatically altered virulence by inhibiting complement deposition and recognition by phagocytes across multiple A. baumannii strains. Thus, capsular structure can determine virulence among A. baumannii strains by altering bacterial interactions with host complement-mediated opsonophagocytosis.